2022
DOI: 10.21776/ub.jpa.2022.010.04.2
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Addition of Red Palm Oil (Rpo) to the Sensory and Chemical Characteristics of Beef Sausage

Abstract: Synthetic antioxidants are widely used to inhibit quality deterioration of the beef sausage. This study utilizes the high carotene content in Red Palm Oil (RPO) as a substitute for vegetable oil in beef sausage. This study aims to determine the sensory and chemical characteristics of beef sausage with the addition of RPO 5%, 10%, and 15%, and obtain the best formulation. Based on the study, it is known that beef sausage with the addition of RPO 10% received the highest overall sensory rating with an average sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…RPOO provided the reddish-yellow color originating from the carotenoid pigments [23]. In this study, the sausage owned the color because of the phenomenon from the RPO [12]. Furthermore, RPO also provided a deep reddish-orange color because of the carotenoids in instant noodle oil seasoning [24].…”
Section: A Colormentioning
confidence: 60%
See 2 more Smart Citations
“…RPOO provided the reddish-yellow color originating from the carotenoid pigments [23]. In this study, the sausage owned the color because of the phenomenon from the RPO [12]. Furthermore, RPO also provided a deep reddish-orange color because of the carotenoids in instant noodle oil seasoning [24].…”
Section: A Colormentioning
confidence: 60%
“…The main different is that the rendang lokan in recent study contained arelatively higher protein as compare to protein content in chicken noodle and siomay in previous study. Various studies reported that the addition or red palm oil (RPO) could boost the carotene content, thus increase vitamin A content in the product [10], [12], [13].…”
Section: Bmentioning
confidence: 99%
See 1 more Smart Citation
“…RPO addition to increase carotenoid content of food has been carried out by previous researchers with different concentrations depending on the type of food. Sorghum cake containing 20% RPO was preferred over the cake with 24% RPO [ 34 ] and beef sausages with 10% RPO were more acceptable than those with 15% RPO [ 35 ]. In this study, based on the panel's discussion, it was concluded that adding 2% RPO, either before or after cooking, could be used as a cooking method to produce rice with a sensory quality similar to or better than regular rice.…”
Section: Resultsmentioning
confidence: 99%